APORFIN SEBUAH ALKALOID DARI POHON HURU (Litsea cordata Sp) JACK (HOOK).F (LAURACEAE) - Budhiman Adi Setyawan (Bina Teknika, 2015)
Litsea cordata Jack (Hook).F is a high tree which grows in West Java.The Alkaloid constituents were isolated from methanol extract , by the usal acid-base extraction to produce a total alkaloid. The total alkaloid was separated into phenolic and non-phenolic fractions with the same way. Two alkaloids components isolated from the phenolic fraction suggested to be , tetrahydro-benzylisokuinolyne derivative and aporphine derivative base on spectroscopic data , UV and mass spectrum.